Application of derivatives market for controlling risks of commodity prices / Išvestinių finansinių priemonių taikymas žaliavų kainų rizikai valdyti - Rasuolė Drazdauskienė; Viktorija Stasytytė (Mokslas: Lietuvos Ateitis, 2015)
The issue of raw milk procurement cost level and fluctuation which inhibits strengthening negotiating positions of dairy product fabricants and probability of them staying competitive in the European Union, is examined. Scientific literature that analyzes risks of staple prices is overviewed in the article. The paper provides statistical data representing the situation of Lithuania in contrast with European Union rates. Global usage of prospective transactions and their possible influence on price regulation are analyzed. After examining statistical data and academic literature, conclusions are provided.